PARTISIPASI SUAMI DALAM PEMBERIAN ASI HUSBAND PARTICIPATION IN BREAST FEEDING - Erna Erawati; Wiwin Reni; Lulut Handayani , Poltekkes Semarang Program Studi Keperawatan Magelang (Jurnal Kebidanan, 2014)
ABSTRACT Participation of the husband has a very large effect to encourage the breast feeding woman, because either the presence or absence of the husband 's participation was crucial in the wife's mental condition. If the husband does not give participation, usually caused by ignorance. The method of this study is cross- sectional with total sampling. Analysis of the data using univariate and bivariate (fisher 's exact test). The results showed that most of husband participation psychologically was in medium category (74,20 %),Â  the financial of husbandâ€™s participation was in the medium category (58,07 %), and the instrumental of husband's participation was in the medium category (54,84 % ). Most respondents did not breastfeed exclusively is 80,65 %. There was a relationship between participation husband with breastfeeding with p < Î± (0,009 < 0,05 ). The results of this study recommends that breast feed mothers often follow counseling conducted health workers. Husbands are expected to know and understand more about breastfeeding problems. Pregnant women should be able to ask and resolve difficulties in breastfeeding so that the mother can give breast milk to their babies after birth. Keywords : Participation husband, breastfeeding, lactation.